Code essentials 2 : guidelines for policy makers on implementing the international code of marketing of breastmilk substitutes and subsequent WHA resolutions - Joo Kean, Yeong; Bardsley, Megan Jessica; Ching, Constance; Allain, Annelies (IBFAN Sdn Bhd, 2018)
A comprehensive guide specifically for governments on how to best implement the International Code. It closely examines each Code article and all relevant WHA resolutions, and provides examples on how they are dealt with in selected countries. A Model Law is included as reference text for countries to adapt and emulate accordingly. Nakladatelská anotace. Kráceno.
Keywords: Marketing; vytváření politiky; World Health Organization; mezinárodní spolupráce; zákonodárství jako téma; Breast Feeding; Světová zdravotnická organizace; Infant Formula; Policy Making; Legislation as Topic; politologie, politika, zdravotní politika; marketing; ekonomie, ekonomika, ekonomika zdravotnictví; International Cooperation; nutriční terapie, dietoterapie a výživa; náhražky mateřského mléka; kojení